Differences of microRNA expression profiles between monozygotic twins' blood samples. (July 2019) - Xiao, Chao; Pan, Chao; Liu, Erliang; He, Huayu; Liu, Chunfeng; Huang, Yujie; Yi, Shaohua; Huang, Daixin
Highlights: The miRNA expression profiles in blood between MZ individuals were compared. 545 differentially expressed miRNAs were found in seven pairs of MZ twins. 29 differentially expressed miRNAs were shared across ≥ 4 pairs of MZ twins. The results of microarray analysis were similar to those of qRT-PCR. Putative targets of 29 differentially expressed miRNAs were predicted. Pathway enrichment of the predicted target genes were also depicted. Abstract: Monozygotic (MZ) twins are widely regarded as genetically identical, and traditional DNA typing methods are insufficient in identifying MZ twins. So the discrimination of MZ twins become a forensic problem. MicroRNAs (miRNAs) are a class of small, endogenous, non-protein-coding RNA molecules of approximately 22 nucleotides in length, and exist extensively in a variety of eukaryotic cells. MiRNAs regulate gene expression and play fundamental roles in multiple biological processes, including cell differentiation, proliferation and apoptosis as well as aging and disease processes. The goal of this study is to explore the differential expression of miRNAs within MZ twin pairs, and aimed to find new biomarkers for distinguishing MZ twins. Thus, the miRNA expression profiles of seven pairs of healthy MZ twins of different sex and age were analyzed by miRNA microarray. A total of 545 miRNAs were found to be differentially expressed in these MZ twin pairs, and 2, 5, 22, 53 and 132 differentially expressed miRNAs were shared across six, five, four, three and two pairs of MZ twins respectively. These findings had been confirmed by real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assays on select miRNAs, including miR-151a-3p, miR-3653-3p, miR-142-3p, miR-4325, miR-16-5p, let-7i-5p, miR-222-3p, miR-550b- 3p, miR-4791 and miR-27a-3p. The results demonstrated that there are differences in the expression of miRNAs within MZ twin pairs, suggesting a role of miRNAs in identifying MZ twins.